New Directions in Internet Management - Purba, Sanjiv (CRC Press, 2009)
What is the business model for making money on the Internet and how does it function? The answer to this question will determine the shape of the Internet over the near term. As the Internet business model continues to evolve, so will Internet management. And with the demise of the Internet greatly exaggerated, it will continue to be a driving force for business in the future. Keeping you up-to-date with the latest thinking in this field, New Directions in Internet Management gives you an encyclopedia of Internet management know-how. Most Internet-related books present in-depth coverage of one particular technology or application. Not this one. It provides you with a strategic and tactical view of the entire Internet landscape, what the technologies and applications are, how they work together, and how to plan for them. You get advice from battle-scarred experts on everything from choosing the right Web database to finding a reliable Web consultant, from security to performance management. Detailed and instructive case studies, examples, and hundreds illustrations supplement the coverage. Focusing exclusively on the management aspects of Internet development and maintenance, New Directions in Internet Management shows you how to leverage Internet technology while abiding by time-honored business practices.